Anthurium comuneros, a new species of Sect. Calomystrium (Araceae) from Colombia - López-Floriano, Oscar Mauricio; Sanín, David; Zuluaga, Alejandro (Phytotaxa, 2026)
A new species of the genus Anthurium section Calomystrium (Araceae) is presented for Colombia. Anthurium comuneros López-Flor., Zuluaga & D. Sanín collected at Santander Department is most similar to A. andreanum Linden ex André, but differs by its rhizome length to 2 m long (vs 1 m long), petioles slightly and sharply sulcate (vs. teretes), peduncle 62−75 cm long (vs 25−45 cm long); and spathe pink to pale light red, ovate-elliptic, apex mucronate (vs bright red, cordate at the base, subrounded, apex long-acuminate). This species is categorized as endangered (EN) according to the conservation status.